Malaria Vaccines Methods and Protocols - Vaughan, Ashley; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Humana, 2015)
This volume focuses on malaria vaccinology, and introduces researchers to a complete overview of the protocols and tools used by molecular and cellular malariologists. The chapters within this book talk about interventions concerning all aspects of life cycle progression--measuring antibody responses to blood stage parasite survival, the T Cell responses engendered by attenuated sporozoite vaccinations, and the unique effect on transmission of antibodies that target the mosquito stage of the life cycle. Additionally, methods concerning the ability to generate targeted gene deletions and replacements in the genome of Plasmodium parasites convey how Plasmodium parasite phenotypes can be created to precise specifications. More recently, the potential power of humanized mouse models of disease progression have been demonstrated and are also discussed in the book. Written in the highly successful Methods in Molecular Biology series format, chapters include introductions to their respective topics, lists of the necessary materials and reagents, step-by-step, readily reproducible laboratory protocols, and tips on troubleshooting and avoiding known pitfalls. Cutting-edge and thorough, Malaria Vaccines: Methods and Protocols is a useful and unique resource for any aspiring malaria vaccinologists because of the volume's exquisitely detailed methodologies that are not typically found in published literature.  .
Isolation of Non-Parenchymal Cells from the Mouse Liver -- Measurement of the T Cell Response to Pre-Erythrocytic Vaccination in Mice -- Characterization of Liver CD8 T cell Subsets that are Associated with Protection against Pre-Erythrocytic Plasmodium Parasites -- Flow Cytometry-Based Assessment of Antibody Function against Malaria Pre-Erythrocytic Infection -- Assessment of Parasite Liver Stage Burden in Human-Liver Chimeric Mice -- Measurement of Antibody-Mediated Reduction of Plasmodium Yoelii Liver Burden by Bioluminescent Imaging -- Detection of Plasmodium Berghei and Plasmodium Yoelii Liver-Stage Parasite Burden by Quantitative Real Time PCR -- Membrane Feeding Assay to Determine the Infectiousness of Plasmodium Vivax Gametocytes -- The Standard Membrane Feeding Assay: Advances Using Bioluminescence -- Agglutination Assays of the Plasmodium Falciparum Infected Erythrocyte -- Antibody-Dependent Cell-Mediated Inhibition (ADCI) of Plasmodium Falciparum: One and Two-Step ADCI Assays -- A Robust Phagocytosis Assay to Evaluate the Opsonic Activity of Antibodies against Plasmodium Falciparum-Infected Erythrocytes -- Miniaturized Growth Inhibition Assay to Assess the Anti-Blood Stage Activity of Antibodies -- Measuring Plasmodium Falciparum Erythrocyte Invasion Phenotypes Using Flow Cytometry -- The In Vitro Invasion Inhibition Assay (IIA) for Plasmodium Vivax -- The Ex Vivo IFN-γ Enzyme-Linked Immunospot (ELISp ot) Assay -- Evaluating IgG Antibody to Variant Surface Antigens Expressed on Plasmodium Falciparum Infected Erythrocytes Using Flow Cytometry -- Inhibition of Infected Red Blood Cell Binding to the Vascular Endothelium -- Evaluation of Pregnancy Malaria Vaccine Candidates: The Binding Inhibition Assay -- High-Throughput Testing of Antibody Dependent Binding Inhibition of Placental Malaria Parasites -- Generation of Transgenic Rodent Malaria Parasites Expressing Human-Malaria Parasite Proteins -- Vaccination Using Gene-Gun Technology.
Keywords: Immunology; Vaccines; Immunology; Vaccine